Privacy and data protection in elderly healthcare: threats and legal warranties - Costa, Ângelo (2012)
The progressive aging of the population requires new kinds of social and medical intervention and the availability of different services provided to the elder population. New applications have been developed and some services are now provided at home, allowing the older people to stay home instead of having to stay in hospitals. But an adequate response to the needs of the users will imply a high percentage of use of personal data and information, including the building up and maintenance of user profiles, feeding the systems with the data and information needed for a proactive intervention in scheduling of events in which the user may be involved. Fundamental Rights may be at stake, so a legal analysis must also be considered.